Instruction of Hunting (about the Thesis of Toma Zarankaitė-Margienė „The Phenomenon of Hunting in the Grand Duchy of Lithuania in the 15th–16th c. (1572): Socioeconomic, Sociopolitical, Mental Aspects“) - Petrilionis, Antanas (Lietuvos istorijos studijos, 2018)
[text in Lithuanian]
Keywords: none